The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.6061/clinics/2019/e858
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality of bone cancer among children, adolescents and young adults of Brazil

Abstract: OBJECTIVES: Bone cancers occur frequently in children, adolescents, and young adults aging 15 to 29 years. Osteosarcoma and Ewing sarcoma are the most frequent subtypes in this population. The aim of this study was to describe incidence and mortality trends of bone cancers among Brazilian children, adolescents and young adults. METHODS: Incidence information was obtained from 23 population-based cancer registries. Mortality data were extracted from the Atlas of Cancer M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Balmant et al ( 14 ). described that breast cancer mortality rates, in Brazil and its regions, in the 2009–2013 period, for adolescents and young adults, were higher for the 25–29 years old range in all regions (above 4.4 per million).…”
Section: Discussionmentioning
confidence: 99%
“…Balmant et al ( 14 ). described that breast cancer mortality rates, in Brazil and its regions, in the 2009–2013 period, for adolescents and young adults, were higher for the 25–29 years old range in all regions (above 4.4 per million).…”
Section: Discussionmentioning
confidence: 99%
“… 8 In Brazil, the median incidence rate of bone cancer was 5.74 per 1,000,000 among children and 11.25 per 1,000,000 among adolescents. 9 In Taiwan, an overall incidence of 6.70 per 1,000,000 person-years was detected for bone sarcomas. 14 In Finland, a nationwide study detected an annual incidence of 1.8 osteosarcomas per 1,000,000.…”
Section: Discussionmentioning
confidence: 99%
“…Bone cancer, with respective incidence and mortality rates of 0.20 and 0.28%, occurs frequently in children, adolescents, and young adults aged 15 to 29 years ( Siegel et al, 2019 , 2020 ). Osteosarcoma, which accounts for 20 to 40% of all bone tumors, are the most frequent morphological subtypes of bone cancer, representing a worldwide and common primary malignant bone tumor in children and adolescents ( Balmant et al, 2019 ; Muller and Silvan, 2019 ). Growing evidence from recent studies has shown that lncRNA Xist is aberrantly regulated in osteosarcoma.…”
Section: The Role Of Lncrna Xist In Cancermentioning
confidence: 99%